EDUKASI PROSES REPRODUKSI UNTUK PEMBERDAYAAN PEMBUDIDAYA LELE: UPAYA MENINGKATKAN PRODUKTIVITAS BENIH DI KABUPATEN KEDIRI - Alimuddin, Alimuddin; Widanarni, Widanarni; Sudrajat, Agus Oman; Nuryati, Sri; Arfah, Harton; Rahmi, Kurnia Anggraini (Universitas Mataram, 2025)
Catfish (Clarias sp.) aquaculture in Kediri Regency, East Java, faces challenges due to the limited availability of high-quality broodstock and the lack of mastery in catfish spawning technologies, such as broodstock selection and the use of natural materials and probiotics to accelerate gonad maturation. These issues formed the basis for implementing a community empowerment program titled